The Influence of Work Patterns on Indicators of Cardiometabolic Risk in Female Hospital Employees. (May 2015) - Kirk, Megan; VanDenKerkhof, Elizabeth; Janssen, Ian; Tranmer, Joan
Abstract : OBJECTIVE: This study explored the associations between work patterns and indicators of cardiometabolic risk in female hospital employees. BACKGROUND: Aspects of work environments potentially influence the health of employees; however, we have a poor understanding of how different hospital work patterns contribute to cardiovascular risk in female employees. METHODS: We conducted a cross-sectional study of 466 female employees from 2 hospitals in Ontario. Data were collected through self-report, physical examination, and use of hospital administrative work data. RESULTS: In the adjusted analyses, full-time work status, extended shift length, and working 35 or more paid overtime hours per year were significantly associated with metabolic syndrome. CONCLUSIONS: Different work patterns increase cardiometabolic risk in female employees, suggesting a need to better monitor the health of the workforce and implement healthy workplace policy.